2015
DOI: 10.1016/j.toxrep.2015.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of endocrine disruption effect of Roundup ® in adrenal gland of male rats

Abstract: The effect of Roundup® on adrenal gland steroidogenesis and signaling pathway associated with steroid production was investigated. Doses of 10, 50, 100 and 250 mg/kg bw/d Roundup® were administered for two weeks to adult male rats. The 10 mg/kg bw/d dose which reduced circulatory corticosterone levels, but did not change food consumption and body weight, was selected for further study. The expression of cholesterol receptor (low density lipoprotein receptor), de novo cholesterol synthesis enzyme (3-hydroxy-3-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 44 publications
3
38
0
Order By: Relevance
“…This condition manifests as fatigue, anorexia, sweating, anxiety, shaking, nausea, heart palpitations and weight loss." ( [29], p. 1084). Based on this list, we created a table showing how these symptoms distributed among KIDNEYFAILURE1 and KIDNEYFAILURE2.…”
Section: Renal Failure and Adrenal Insufficiencymentioning
confidence: 99%
See 4 more Smart Citations
“…This condition manifests as fatigue, anorexia, sweating, anxiety, shaking, nausea, heart palpitations and weight loss." ( [29], p. 1084). Based on this list, we created a table showing how these symptoms distributed among KIDNEYFAILURE1 and KIDNEYFAILURE2.…”
Section: Renal Failure and Adrenal Insufficiencymentioning
confidence: 99%
“…Guided by a recent paper studying the effects of small doses of Roundup ® on rats [29], we decided to investigate how our two renal failure subsets distributed with respect to symptoms related to adrenal insufficiency. Pandey et al [29] showed that 10 mg/kg doses of Roundup ® administered over a two-week period to male rats resulted in a marked drop in steroidogenesis in the adrenal glands.…”
Section: Renal Failure and Adrenal Insufficiencymentioning
confidence: 99%
See 3 more Smart Citations